ANTHROPOLOGICAL MEASURING OF COMMUNICATIVE – INFORMATIVE CONSCIOUSNESS OF SENSE OF OBJECTIVE REALITY - Vera I. Aksenova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the article is to introduce the anthropological aspects of the communicative and information understanding of the meaning of life; to define the anthropological measurements of communicative and information understanding of the meaning of life connected with the introduction of information and informatization: to consider the models of the development of the information society which are introduced in the developed countries of the world for the solution of the anthropological problems; to analyse the problems of the new meaning of life connected with the development of the information society, and to find the ways of their optimization. Methodology. The new anthropological measurements of socialization of a person are revealed thanks to the analysis of the cognitive structures and epistemes. These measurements consist of mastering of codes and genres of the external discourse. Scientific novelty. The author offers the thesis that the social behaviour of people is significantly defined by the possible sign systems which are created by cultures of the concrete societies that represent a new approach in understanding of the communicative and information determinants of the semantic and vital key points of the person and society. The last ones are determined by the expansion of the communicative and information space which demands the formation of the new anthropological basis of life according to which a person enters socialization and forms a new way of life. Conclusions. Anthropological measurements of communicative and information understanding of the meaning of life are reduced to the fact, that they are affected by the network culture, the new types of communication caused by the information technologies, therefore there is a new type of the person – the virtual or network ones. The formation of the personality is defined by the procedure of interpretation which allows to establish within the discursive space the semantic meanings with a particular situation and thanks to that to reach joining external structures of sociocultural life with the inner world. Thus, the personality forms new conditions for the expansion of freedom, transfer and development of the sociocultural examples of behaviour and cognition, the unconscious phenomena which influence the process of formation of the personality and his/her identity. There is a formation of a person who meets the requirements of the network society and as a result – a global identity is being formed.